PENGEMBANGAN MEDIA KOKAREL (KOMIK KARTUN ELEKTRONIK) MATERI SIKLUS HIDUP TUMBUHAN KELAS IV SEKOLAH DASAR - Neyla Noer Ainy; Abdul Aziz Hunaifi; Muhamad Basori (Jurnal Manajemen Pendidikan, 2026)
This research and development aims to determine the validity, practicality, and effectiveness of the KOKAREL (Electronic Cartoon Comic) media for the life cycle of plants for grade IV of Elementary School. This research and development uses the ADDIE model which consists of the stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of this research were teachers and 32 grade IV students of SDN 1 Grogol, Kediri Regency. The data analysis techniques used were qualitative and quantitative descriptive analysis. The results of this research show that (1) The results of the validity test of material experts were 90% and media experts were 86%, both scores obtained showed very valid criteria. (2) The results of the practicality test showed a percentage of teacher response scores of 92%. Then, the results of the student practicality test in the limited trial obtained a percentage of 82.8% and the student practicality test in the broad trial obtained a percentage of 86.4%. The results of the practicality test for teachers and students showed very practical criteria. (3) The results of the effectiveness test in the limited trial obtained an average pretest score of 66.4 and an average posttest score of 81.4. Then, in the extensive trial, an average pretest score of 69.2 and an average posttest score of 84 were obtained. This shows an increase in learning outcomes before and after using the KOKAREL (Electronic Cartoon Comic) learning media.